Exploring the Expression of Survivin on Neoadjuvant Chemotherapy in Invasive Breast Carcinoma - Rustamadji, Primariadewi; Wiyarta, Elvan; Anggreani, Ineke (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Biomarkers are required to monitor the response to neoadjuvant chemotherapy (NC) in patients with invasive breast cancer (IBC). The purpose of this study is to determine the function of Survivin in the administration of NC, both taxane- and non-taxane-based, to patients with IBC. Methods: Thirty-one samples were categorized according to the NC’s administrative status (before or after) and the type of NC used (taxane- or non-taxane-based). Age, tumor grade, receptor status (ER, PR, HER2, Ki-67), and survivin expression were evaluated. Survivin expressions were evaluated by IHC staining and categorized according median H-score cut-offs, while other data were collected from archives. Data was gathered and analyzed using generalized linear model. Results: Survivin expression decreased following NC administration, although not significantly (p=0.285). The taxane group had lower survivin expression. Statistically, this was not significant (p=0.329). The non-taxane group had the same outcome (p=0.792). The decline in survivin expression was greater in the taxane group than in the non-taxane group, although it was not statistically significant (p=0.369). Conclusion: Although the changes in survivin expression were not statistically significant, when clinical and laboratory data are analyzed, survivin expression has the potential to be a predictive biomarker of NC response as well as clinical outcome in IBC.